Rethinking industrial relations in Malaysia / Kuldip Singh - Singh, Kuldip (Universiti Teknologi MARA, Sarawak, 2005)
Malaysian Industrial Relations is at the crossroads as a result of globalization and the emerging knowledge economy. This article begins with the background of industrial relations theory and Malaysian industrial relations. It also explains changes that are occurring as a result of the changing nature of work and the labour market in response to changes in the global business environment. A number of issues are addressed which call for attention in re-designing a new industrial relations policy for Malaysia in the 21st century.